Cognitive Interpretation Bias: The Effect of a Single Session Moderate Exercise Protocol on Anxiety and Depression - Clarke, Séraphine C.; Cooper, Nicholas R.; Rana, Mirinalee; Mackintosh, Bundy (Frontiers in Psychology, 2018)
Research conducted within the Cognitive Bias Modification (CBM) paradigm has revealed that cognitive biases such as negative cognitive interpretation biases contribute to mental health disorders such as anxiety (Beard, 2011). It has been shown that exercise reduces anxiety (Ensari, Greenlee, Motl, & Petruzzello, 2015). Exercise has also been found to reduce negative cognitive attention biases (Tian & Smith, 2011), however no research to date has investigated the effect of exercise on cognitive interpretation bias. The key aims of the current project is to investigate whether moderate exercise reduces self-reported symptoms of depression and stress. Additionally, to establish which intensity of exercise is required to achieve anxiety reduction and reduce an individual’s negative cognitive interpretation biases. Study one recruited a healthy sample of adult participants who were randomly assigned to one of two conditions: a walking exercise protocol or a control condition (n=2x12). Participants completed anxiety and cognitive interpretation bias measures before and after the walking exercise or control condition. Those in the walking exercise condition presented less symptoms of trait anxiety on a measure of state and trait anxiety inventory (STAI), compared to controls relative to baseline measures following the intervention. Study two recruited frequent exercisers who were assigned to an exercise or control group (n=2x24). Participants completed anxiety, depression, psychological stress and cognitive interpretation bias measures before and after the exercise or control condition. Following the intervention, negative interpretation biases decreased in the exercise group and stayed stable in the control group. The exercise group also had significantly decreased anxiety, depression and stress measures after the exercise condition, whilst controls did not. The research concludes that CBM holds promise for the management of mood disorders and exercise is an effective accompaniment to psychotherapy.